2017
DOI: 10.21873/anticanres.11544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tumor Markers and Their Impact on Prognosis in Gallbladder, Bile Duct and Cholangiocellular Carcinomas – A Pilot Study

Abstract: The results of this study suggested the importance of tumor markers for assessment of prognosis (OS or DFI) in patients with gallbladder carcinoma, bile duct carcinoma, and cholangiocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…[ 11 ] These markers have been used individually for the diagnosis of GBC, but the results have been inconsistent and better sensitivity was observed when used in combination. [ 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] These markers have been used individually for the diagnosis of GBC, but the results have been inconsistent and better sensitivity was observed when used in combination. [ 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that CEA levels can be used for predicting metastasis although few contradictory reports exist [ 18 20 ]. High CEA levels are observed in cancers, whereas changes are also observed in smoking, inflammation, pregnancy, gynecological disease and hepatitis conditions [ 21 , 22 ]. Furthermore, prognostic potential of pre-post-CEA ratio has been reported for CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 8 ] The most commonly used ones are serum carbohydrate antigen 19-9 (CA19-9) and carcinoembryonic antigen (CEA), which only have sensitivities of 50% and 30%, respectively. [ 9 ] Therefore, searching for a highly specific and sensitive diagnostic biomarker for EHCC is urgently needed as this could lead to earlier diagnosis and improved outcome. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%